2021
DOI: 10.1016/j.sjbs.2021.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and in silico study of leaf and bark extracts from Aphanamixis polystachya against common pathogenic bacteria

Abstract: Aphanamixis polystachya may be a natural, renewable resource against antibiotic-resistant bacterial infections. The antibacterial activity of A. polystachya leaf and bark extracts was investigated against three antibiotic-resistant bacterial species and one fungus. Methanolic leaf extract showed only limited antibacterial activity but both methanolic and aqueous bark extract showed high antimicrobial activity. In an antioxidant activity test, leaf and bark extracts exhibited 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 78 publications
1
0
0
Order By: Relevance
“…Sultana et al (2009) also found that bark methanol extract of A. polystachya revealed maximum free radical scavenging activity (IC50 5.36 ppm) was much stronger than our results using leaf extract (IC50 916.378 ppm). In line with Krishnaraju et al (2009), A. polystachya bark extracts exhibited better efficacies toward free radical agent compared to vitamin C. This is in accordance with Paul et al (2021) which found that bark extracts offer more antioxidative activity than leaves extracts.…”
Section: Weaksupporting
confidence: 85%
“…Sultana et al (2009) also found that bark methanol extract of A. polystachya revealed maximum free radical scavenging activity (IC50 5.36 ppm) was much stronger than our results using leaf extract (IC50 916.378 ppm). In line with Krishnaraju et al (2009), A. polystachya bark extracts exhibited better efficacies toward free radical agent compared to vitamin C. This is in accordance with Paul et al (2021) which found that bark extracts offer more antioxidative activity than leaves extracts.…”
Section: Weaksupporting
confidence: 85%